The Reddish, Iron-Rust Color of the Native Americans. Immanuel Kant’s Racism in Context - van Gorkom, Joris (Con-Textos Kantianos. International Journal of Philosophy, 2019)
In this essay, I discuss Kant’s views on the “American race.” Robert Bernasconi has pointed out that more research on the sources of Kant’s ideas on non-white races is needed in order to have a better understanding of his racism. This essay responds to that call in order to show how Kant contributed to on-going discussions on the causes and meaning of human differences. However, I will also focus on his influence on his contemporaries. The reason for doing so is two-fold. Firstly, I will question Irene Tucker’s recent attempt to show that skin color was considered a racial sign because of its supposed self-evidence and immediate legibility. By way of a presentation of Kant’s views on the “American race,” I will show that race mixing formed the core of Kant’s racial theory and not the alleged immediacy of racial sight. Secondly, I will focus on his influence in order to question the popular idea that Kant had in his late work developed second thoughts on his racial hierarchy. His appraisal of the work of one of his contemporaries (Christoph Girtanner) clearly shows that the matter is far more complicated than suggested in these interpretations of Kant’s racial work.